Moral Blueprint or Neoliberal Gobbledygook?: Civil Society Frames among Polish Think Tanks. (November 2015) - Jezierska, Katarzyna
Poland is often pointed to as the regional leader of transition processes with regard to the development and sustainability of civil society. This article presents a critical perspective on the direction in which Polish civil society has evolved after 1989. The author reconstructs existing frames of civil society within Polish elite NGO discourse and argues that one specific understanding of civil society—civil society as third sector/service provision—has gained a hegemonic position, marginalizing other conceptions and thus other functions of civil society. Civil society as moral blueprint, civil society as control power, and civil society as neoliberal gobbledygook are identified as coexisting, potentially counter-hegemonic frames. Thus, the quasi-public function, that is, providing services that the state does not, has become the dominant understanding of civil society suppressing its socialization and political functions, once so prominent in Central and Eastern Europe.